Capital and liquidity buffers and the resilience of the banking system in the euro area - Katarzyna Budnik; Paul Bochmann (European Central Bank (ECB), 2017)
How do capital and liquidity buffers affect the evolution of bank loans in periods of financial and economic distress? To answer this question we study the responses of 219 individual banks to aggregate demand, standard and unconventional monetary policy shocks in the euro area between 2007 and 2015. Banks' responses are derived from a factor-augmented VAR, which relates macroeconomic aggregates to individual bank balance sheet items and interest rates. We find that banks with high capital and liquidity buffers show a more muted response in their lending to adverse real economy shocks. Capital and liquidity buffers also affect bank responses to monetary policy shocks. High bank capitalisation reduces the degree to which banks increase the average duration of loans to the non-financial corporate sector, while high bank liquidity strengthens the positive response to policy easing of both long- and short-term loans to the non-financial corporate sector. The latter findings substantiate the relevance of interactions between prudential controls and monetary policy.
Keywords: E51; E52; G21; 330; macroprudential policy; monetary policy; capital requirements; liquidity requirements